The Livelihood curriculum development for enhancing agricultural worker in self-reliance - Khuana, Khwanchai; Boontongtherng, Asst.Prof.Dr.Poosit; Rittidet, Asst.Prof.Dr.Prasopsuk (Journal for Developing the Social and Community, 2015)
This research aims to develop curriculum for enhancing a Agricultural worker in selfreliance research was divided into four steps by employing research and development. The statistics used for analysis data were mean ( X ), percentage, standard deviation (S.D.) and t – test (dependent samples). The research was presented in the form of descriptive analysis. The research results were found that : 1. This curriculum has been consisted of 10 components, 8 learning units and consuming 19 hours’ time. The contents have been based on righteous–vocation on the topic of “ Laying-chicken Raising” . 2. The post test scores had higher than pre test scores with statistical significance at the level of .05. All agriculturists gained testing scores 80% up. The agriculturists’ self–dependence was found at most level. Their satisfaction in learning accordingly to righteous–curriculum was found at most level.